2022
DOI: 10.47191/jefms/v5-i7-11
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Application of Green Accounting in Endek Craft SMEs in Klungkung Regency, Bali Province

Abstract: Culture and the environment greatly affect the types of products sold by SMEs, Klungkung Regency is one of the areas producing Balinese woven fabrics, namely endek, endek fabric is the main commodity that is the flagship product of the Province of Bali. Law No. 23 of 1997 stipulates that every business entity and person carrying out commercial economic activities must be able to carry out environmental care. Green Accounting is an accounting activity that includes and calculates the costs of prevention and cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a qualitative study conducted in Bali province, Adyatma et al (2022) revealed that small and medium enterprises (SMEs) in Bali have limited understanding and application of GA in their business practices. Typically, these SMEs still handle waste in a traditional manner, which is less professional compared to larger enterprises.…”
Section: Factors Affecting Ga and The Application Of Gamentioning
confidence: 99%
“…In a qualitative study conducted in Bali province, Adyatma et al (2022) revealed that small and medium enterprises (SMEs) in Bali have limited understanding and application of GA in their business practices. Typically, these SMEs still handle waste in a traditional manner, which is less professional compared to larger enterprises.…”
Section: Factors Affecting Ga and The Application Of Gamentioning
confidence: 99%